A New Quantitative Cell-Based Assay Reveals Unexpected Microtubule Stabilizing Activity of Certain Kinase Inhibitors, Clinically Approved or in the Process of Approval - Ramirez-Rios, Sacnicte; Michallet, Sophie; Peris, Leticia; Barette, Caroline; Rabat, Clotilde; Feng, Yangbo; Fauvarque, Marie-Odile; Andrieux, Annie; Sadoul, Karin; Lafanechère, Laurence (Frontiers in Pharmacology, 2020)
Agents able to modify microtubule dynamics are important anticancer drugs. The absence of microtubules resulting from drug-induced depolymerization is easy to detect. However the detection of a stabilized microtubule network needs specific assays since there is not a significant visual difference between a normal and stabilized microtubule networks. Here, we describe a quantitative cell-based assay, suitable for automation, which allows the detection of stabilized microtubules without the need of microscopic examination. The rationale of this assay is based on the drug-induced resistance of the microtubule network to the depolymerizing agent combretastatin A4 and the subsequent detection of the residual microtubules by immunoluminescence. Using this assay to screen a kinase inhibitor library allowed the selection of seven known kinase inhibitors: selonsertib, masatinib, intedanib, PF0477736, SNS-314 mesylate, MPI0479605, and ponatinib. The yet undescribed ability of these inhibitors to stabilize cellular microtubules was confirmed using additional markers of stable microtubules and time-lapse video-microscopy to track individual microtubules in living cells. None of the compounds interacted, however, directly with tubulin. By employing other inhibitors of the same kinases, which have structurally unrelated scaffolds, we determined if the microtubule stabilizing effect was due to the inhibition of the targeted kinase, or to an off-target effect. Many of these inhibitors are clinically approved or currently assayed in phase 2 or phase 3 clinical trials. Their microtubule-stabilizing effect may account for their therapeutic effect as well as for some of their adverse side effects. These results indicate also a possible repurposing of some of these drugs.